THE EFFECT OF FAMILY THERAPY TOWARD PREVENTION OF VIOLENT BEHAVIOR IN CHILD: A LITERATURE REVIEW - Herman, Herman; Kusbaryanto, Kusbaryanto (Universitas Respati Yogyakarta, 2020)
Family is lasting a social group based on marriage and blood relations. The family plays an important role in the inheritance of the noble values of life for future generations. A healthy family will contribute to the development of a healthy society. This aims to find out the effect of the education system of family therapy on the prevention of violence in children. This research uses relevant Literature review which is reviewed following the search from 3 databases. They are ProQuest, ScienceDirect, and Google Scholar. The search year is limited to the last 5 years from 2014-2019 to ensure the latest included research, using the keyword